Prevention, Management and Resolution of Political Conflicts in Nigeria: The Polite Language Approach - Nwabunze, Donatus Chijioke; Obi, Ngozi M. (South Asian Journal of Social Sciences and Humanities, 2020)
As it has been observed by Aristotle centuries ago, of all the animals on earth, humans are the only  beings endowed with the capacity to talk. They can as well use and manipulate diverse tools for various  purposes. But the most important tool that makes them unique from other animals is their capacity to  make use of speech to interact. Man is language; language is man. As social beings’ people cannot get  along in the society without it, as far as communication is concerned. However, apart from positive  functions of language, it can also perform negative functions when used offensively. It can be used both  as constructive and destructive tool. The world over, offensive language leads to conflict –serious  disagreement, quarrel or dispute between one person and another, between two groups of people, and  even between nations. Interestingly language can equally be used to prevent, control, manage or settle  disputes. It is the view of this paper that global conflicts, with particular reference to Nigeria, can be  prevented, controlled and managed if the citizens can learn to use language constructively in a manner  that does not slur and smear others. This paper further argues that inter-personal, ethnic and national  conflicts can be curbed in Nigeria with skillful application of polite language in any communication  event. Conclusively, this paper is of the view that the avoidance of conflict-inducing language would  enhance fellowship of Nigerian citizens, rather than fellowship of race, ethnicity, religion and class in  the country. As an empirical study, the research has Brown and Levinson’s politeness theory, and  Deborah Cameron’s verbal hygiene theory, as theoretical frameworks. It is hoped that the study will  complement all the efforts government has been making in the prevention, management and resolution  of various politically motivated conflicts which are threatening the corporate existence of Nigeria as a  nation.
Keywords: Conflict; Language; Prevention; Management; Resolution